Edible bird's nest soup (EBNS) attenuates glomerular basement membrane thickening and tubular NF-κβ and NLRP3 expression in the acute renal injuries linked to obesity in rats - Akmal, Mohd Noor; Intan-Shameha, Abdul Razak; Bakar, Zuki Abu; Ajat, Mokrish (John Wiley and Sons, 2025)
This study aimed to elucidate how edible bird's nest soup (EBNS) and edible bird's nest extract (EBNE) can protect the kidneys of obese rats from acute kidney injuries caused by a high-fat diet (HFD) via histological techniques. A total of 24 male Sprague–Dawley rats aged 12 weeks old were utilized in this study. The rats were randomly assigned (n = 6) to either the chow diet; HFD; HFD + EBNS (843.2 mg/kg); or HFD + EBNE (6.5 mg/kg) for 12 weeks. Body mass gain and visceral adipose tissue (VAT) were measured, and the kidneys were collected for histopathological analysis, including H&E, PAS staining, and immunohistochemistry (TLR4, NF-κβ and NLRP3). Results showed the EBNS group maintained normal body mass (530.19 ± 0.32) via the reduction of VAT (28.79 ± 0.24) influx, similar as in the BC group (527.78 ± 0.77; 30.61 ± 0.91). Meanwhile, the EBNE group demonstrated significant body mass gain (597.04 ± 0.52) and VAT (45.03 ± 0.38) deposition. The glomeruli diameters (104.76 ± 2.77) in the EBNS group were normal compared to those in the EBNE group (142.05 ± 1.51), which showed glomerulomegaly and membranous glomerulonephritis. In the EBNE group, the NF-κβ and NLRP3's immunoreactivity covered as much as 44.38% ± 0.21% and 60.77% ± 0.53%, respectively, in the tissue section. Meanwhile, the EBNS group observed only 2.85% ± 0.82% (NF-κβ) and 6.80% ± 0.62% (NLRP3) immunoreactivity in the tissue. These findings were consistent with mild (1.83 ± 0.70) and moderate (5.65 ± 0.30) tubular inflammatory cell infiltration in the EBNS and EBNE groups, respectively. In the obese rat model induced by HFD, the EBNS was able to prevent the obesity-related acute kidney injuries by maintaining a normal architecture of glomerular histomorphology and suppressing the tubular NF-κβ and NLRP3 expression.